Aberrant brain network connectivity related to cognitive and emotional regulation in women with abdominal obesity - Qifu Li; Gaoyangzi Huang; Siwen Zhao; Shumin Zhang; Ziwen Chen; Xin Tang; Xianmei Pei; Ruqin Yang; Zili Liu; Rui Hu; Diwei Tang; Chonghui Xing; et al. (Scientific Reports)
Abstract Abdominal obesity (AO) exhibits unique endocrine and metabolic characteristics in women, yet its neural mechanisms remain unclear. The aim of this study was to investigate the neural mechanisms of AO in females by examining functional connectivity (FC) alterations across brain networks. Resting-state functional MRI (rs-fMRI) data were collected from 38 female AO patients and 24 healthy controls (HCs). Independent component analysis (ICA) was utilized to evaluate FC and functional network connectivity (FNC) within and between brain networks. FC analysis revealed significant alterations within the default mode network (DMN), ventral attention network (VAN), and visual network (VN) (p < 0.05, FDR corrected). In the DMN, increased FC was observed in the left posterior cingulate gyrus and left angular gyrus, while decreased FC was found in the left precuneus and right posterior cingulate gyrus. The VAN and VN showed reduced FC in regions associated with attention control and visual processing, including the left inferior parietal gyrus, left inferior frontal gyrus, triangular part, and left calcarine fissure and surrounding cortex. Internetwork analysis identified significantly higher FNC between the DMN and left frontoparietal network in female AO patients (p < 0.001). This study revealed significant abnormalities in brain functional connectivity in female AO patients, particularly in networks related to self-referential processing, attention, and decision-making. These findings provide a neural basis for cognitive and emotional dysregulation in AO and highlight the potential for targeted interventions to improve self-regulation and inform prevention and treatment strategies.